PREVALENCE AND ASSOCIATED FACTORS OF DEPRESSION MEASURED BY THE HAMILTON DEPRESSION RATING SCALE AMONG WORKING-AGE ADULTS WITH VESTIBULAR DISORDERS (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the prevalence of depression and analyze its associated factors among inpatients aged under 60 years with vestibular disorders treated at the Department of Neurology, Bach Mai Hospital.Methodology: The cross-sectional study was conducted on 91 inpatients diagnosed with vestibular disorders at the Department of Neurology, Bach Mai Hospital, from August 2024 to March 2025. The Hamilton Depression Rating Scale (HAM-D) was utilized to classify and assess depression levels among these patients.Results: the prevalence of depression in patients with disorder of vestibular function was 20.9%.  Longer disease duration (p
Keywords: HAM-D, depression, vestibular dysfunction.